A multi-stimulus-responsive bionic fish microrobot for remote intelligent control applications. Issue 5 (10th January 2023) - Yang, Wenguang; Wang, Xiaowen; Wang, Zhen; Yuan, Zheng; Ge, Zhixing; Yu, Haibo
Abstract : A multi-stimulus-responsive bionic fish microrobot was fabricated using CNTs, pNIPAM, and magnetic nanoparticles for remote intelligent applications. Abstract : In nature, all creatures have their unique characteristics that allow them to adapt to the complex and changeable living environments. In recent years, bionic fish has received increased attention from the research community, and many fish-like microrobots driven by the Marangoni effect have been developed. They are generally characterized by easy operation and rapid driving. However, traditional fish-like microrobots can only be driven by a single stimulus and move on two-dimensional (2D) gas–liquid interfaces, which greatly limits their ability in obstacle avoidance and transportation. In this article, we propose a multi-stimulus-responsive bionic fish microrobot, which is made of temperature-responsive hydrogel poly( N -isopropylacrylamide) (pNIPAM). This microrobot is impregnated with carbon nanotubes (CNTs) and Fe3 O4 and therefore has magnetic and photothermal conversion properties. Under the action of optical, magnetic or ethanol molecules, the microrobot can perform complex programmable translational motion on 2D surfaces and controllable rising and sinking, while realizing motion simulation and obstacle avoidance. The microrobot is expected to be used for a wide range of applications in intelligent control systems.